Des mots appelés à la barre : vocabulaire du droit - Le Barreau du Québec et ses avocats (Office québécois de la langue française, 2023)

La diffusion des sources du droit en anglais et en français au Cameroun - Fandjip, Olivier; Boog Massock, Valencia Alex (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2022)
Comme d’autres pays africains jadis sous domination, le Cameroun a, après son indépendance, adopté comme langues officielles celles des puissances tutélaires. L’adoption de la loi du 24 décembre 2019 portant promotion desdites langues amène à s’interroger sur l’incidence de celle-ci sur la diffusion des normes. L’efficacité de la contribution de ces langues à la diffusion des sources du droit dépend de l’amélioration du cadre de cette diffusion. Une étude basée sur la méthode juridique ainsi que la technique documentaire montre que l’anglais et le français ont été réaffirmés comme système d’expression en matière de diffusion des sources du droit. Cependant, des limites, notamment d’ordre socioculturel, nuisent à son efficacité. Le renforcement de la promotion de ces langues ainsi que l’ouverture sur les langues nationales peuvent favoriser son amélioration. Cameroon, like many African countries once under domination, has, after its independence, adopted the languages of these tutelary powers as official languages. The question is whether these languages contribute to a better dissemination of the sources of law. The effectiveness of the contribution of these languages to the dissemination of the sources of law depends on the improvement of the framework for such dissemination. A study based on the legal method as well as the documentary technique shows that English and French, as a system of expression in the dissemination of the sources of law, both through advertising and beyond it, contribute to this dissemination. However, limitations, particularly of a socio-cultural nature, hinder its effectiveness. Strengthening the promotion of these languages and opening up to national languages can help to improve it.
Keywords: Diffusion; Droit traditionnel; Droit écrit; Langues nationales; Langues officielles; Modern law; National languages; Normes de droit; Official languages; Publicité; Sources du droit; Sources of law; Traditional rules

Story of a legal codex(t) : writing law in code - Ma, Megan (Institut d'études politiques, 2021)
How is the law measured? For long, it appeared that the law cannot be measured. While there are standards and processes, the law was not regarded as quantifiable. Only in the advent of recent technological advancements in law have there been considerations for metrics. These technologies sought to tackle the legal field’s inherent protectionism fueled by deep asymmetries in information. Consequently, the rise in legal ‘metrics’ stems from an access to justice perspective. The assumption is that in making the law more quantifiable, knowledge that has been historically opaque and inaccessible outside of the legal community may be revealed.Alternatively, it may be argued that the law has always been measurable. Words, through linguistic devices, have shaped legal meaning. In effect, the law conceivably has been measured by its words. In fact, “law exists as text” (Hildebrandt, 2015). I further this line of thinking by investigating natural language as the key vessel through which the law has manifested itself. Does the law depend on natural language to do its work? Importantly, is the language sufficient at housing legal norms?This dissertation seeks to tell a narrative. Broadly, it chronicles the story of law’s intimate relationship with language. But more specifically, the thesis details the law’s recent encounter with the digital. When law met technology, its relationship with language changed, invoking skepticism around its fitness for the conveyance of legal concepts. With the introduction of an innovative player – code – the law had perceivably found its new linguistic match. As a result, code was tested for its ability to perform and accommodate for the law’s demands. Ultimately, confronted by natural language and code, the law is asked whether code can be its language. Comment mesure-t-on le droit ? Longtemps, le droit semblait résister à la mesure. Bien qu'il existe des normes et des processus, le droit n'était pas considéré comme quantifiable. Ce n'est qu'avec l'avènement des récentes avancées technologiques dans le domaine du droit que l'on a commencé à envisager une telle quantification. Ces technologies ont cherché à s'attaquer au protectionnisme inhérent au domaine juridique, alimenté par de profondes asymétries d'information. Par conséquent, l'essor de la "métrique" juridique découle d'une perspective d'accès à la justice. L'hypothèse est qu'en rendant le droit plus quantifiable, des connaissances historiquement opaques et inaccessibles en dehors de la communauté juridique peuvent être révélées.On peut également faire valoir que le droit a toujours été mesurable. Les mots, par le biais de dispositifs linguistiques, ont façonné la signification juridique. En effet, il est concevable que le droit ait été mesuré par ses mots. En effet, "le droit existe en tant que texte" (Hildebrandt, 2015). J'approfondis cette ligne de pensée en examinant le langage naturel en tant que vecteur clé à travers lequel le droit s'est manifesté. La loi dépend-elle du langage naturel pour faire son travail ? Plus important encore, le langage est-il suffisant pour abriter les normes juridiques ?Cette thèse cherche à raconter une histoire. De manière générale, elle relate l'histoire de la relation intime du droit avec le langage. Mais plus spécifiquement, la thèse détaille la rencontre récente du droit avec le numérique. Lorsque le droit a rencontré la technologie, sa relation avec le langage a changé, suscitant le scepticisme quant à son aptitude à transmettre des concepts juridiques. Avec l'introduction d'un acteur innovant - le code - le droit a visiblement trouvé sa nouvelle adéquation linguistique. En conséquence, le code a été mis à l'épreuve quant à sa capacité à fonctionner et à répondre aux exigences du droit. Finalement, confronté au langage naturel et au code, le droit se demande si le code peut être son langage.
Keywords: Connaissance du contexte; Contextual knowledge; Droit et informatique; Informatique; Langage juridique (informatique); Langages de programmation; Law and computation; Linguistics; Linguistique; Programming languages

Legal Translaboration for Effective Intercultural Communication - Bell Mandeng, Adrien (Scientific Annals of Alexandru Ioan Cuza University, 2021)
The European-inspired bilingualism and bi-legal system in Cameroon lead to an irregular profile and may be interesting for the European Union (EU) in its quest for preservation of intercultural processes through translation. The Organization for the Harmonization of Business Law in Africa (OHADA) of which Cameroon is part is only affiliated to Civil Law. However, the two legal systems employed in Cameroon (where both Civil Law and Common Law are used) are based on a balance in what concerns the conceptual, epistemic and stylistic representation. Intercultural dysfunction is the consequence of the lack of methodology in legal translation. Collaboration between legal translators and practitioners is key to adopt an agreed-upon model in multilingualism.
Keywords: Culture; History; Intercultural communication; Legal translaboration; OHADA